On the use of high aspect ratio finite elements to model hydraulic fracturing in deformable porous media - Manzoli, Osvaldo L. [UNESP]; Cleto, Pedro R. [UNESP]; Sánchez, Marcelo; Guimarães, Leonardo J.N.; Maedo, Michael A. (Elsevier, 2019)
Hydraulic fracturing is a technique based on the injection of a viscous fluid at high pressure into an engineered well with the intention of initiating and propagating multiple fractures in a rock formation containing hydrocarbons to increase well-reservoir connectivity. This work proposes a framework to simulate the initiation and propagation of hydraulically induced fracture based on the Continuum Strong Discontinuity Approach (CSDA) and solid finite elements with high aspect ratio (HAR) in the context of conventional continuum constitutive (stress–strain) relationships (based on damage theory). The porous media considered here are deformable and the hydro-mechanical problem is solved in a fully-coupled manner. Full details about the proposed continuous approach to model hydraulic fractures are presented, including the finite element equations and their approximations. The new approach is validated against analytical and numerical solutions. Moreover, the influence of the dimensions of the HAR interface elements on the results is also investigated.
Keywords: Continuum damage model; Continuum strong discontinuity approach; Finite elements with high aspect ratio; Hydraulic fracturing; Hydro-mechanical coupling